Endonasal endoscopic nasopharyngectomy for the treatment of nasopharyngeal papillary adenocarcinoma: Report of a rare case. (January 2018) - Ünsaler, Selin; Başaran, Bora; Aslan, Ismet; Yilmazbayhan, Dilek
Abstract: We report a case of low-grade nasopharyngeal papillary adenocarcinoma in a 9 year-old male that was diagnosed incidentally after an adenoidectomy procedure and treated with endonasal endoscopic nasopharyngectomy without any adjuvant therapy. The patient has been followed up for 3 years with no evidence of recurrence. We point out the importance of preoperative fiberoptic nasopharyngoscopy in the absence of longstanding symptoms in school-aged children and histopathologic examination of adenoidectomy specimens in the presence of atypical findings. We also suggest endonasal endoscopic resection in case of papillary adenocarcinoma.